2017
DOI: 10.1073/pnas.1618935114
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cu surfaces for the electrocatalytic conversion of CO 2 : Controlling selectivity toward oxygenates and hydrocarbons

Abstract: In this study we control the surface structure of Cu thin-film catalysts to probe the relationship between active sites and catalytic activity for the electroreduction of CO 2 to fuels and chemicals. Here, we report physical vapor deposition of Cu thin films on large-format (∼6 cm 2 ) single-crystal substrates, and confirm epitaxial growth in the <100>, <111>, and <751> orientations using X-ray pole figures. To understand the relationship between the bulk and surface structures, in situ electrochemical scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
347
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(370 citation statements)
references
References 32 publications
21
347
2
Order By: Relevance
“…Cu thin films with specific crystal orientations were prepared by rf sputtering of Cu onto silicon (Si) single crystal substrates. This approach is based on previous studies demonstrating the epitaxial relationship between Cu and Si substrates of different orientations ,,. Cu(100)‐oriented thin films were used for the present study because it has been shown that this surface exhibits a high selectivity to the desired C 2+ hydrocarbons and oxygenates (e.g., C 2 H 4 and CH 3 CH 2 OH) and has been shown to be electrochemically stable .…”
Section: Methodsmentioning
confidence: 99%
“…Cu thin films with specific crystal orientations were prepared by rf sputtering of Cu onto silicon (Si) single crystal substrates. This approach is based on previous studies demonstrating the epitaxial relationship between Cu and Si substrates of different orientations ,,. Cu(100)‐oriented thin films were used for the present study because it has been shown that this surface exhibits a high selectivity to the desired C 2+ hydrocarbons and oxygenates (e.g., C 2 H 4 and CH 3 CH 2 OH) and has been shown to be electrochemically stable .…”
Section: Methodsmentioning
confidence: 99%
“…Epitaxially grown Cu thin films were used as electrocatalysts in order to have well-defined catalytic surfaces. 27 These films were prepared by radio-frequency sputtering of Cu onto silicon (Si) single crystal substrates, taking advantage of the epitaxial relationship between Cu and Si substrates of different orientations. [27][28] Most of our studies were conducted on the Cu(100) surface because it has been…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The Cu(100) surface exhibits an activity for generating C 2+ products roughly an order of magnitude higher than that for Cu(111), as reported elsewhere. 13,16 This facet dependence can cause polycrystalline Cu foils obtained from different vendors or even different batches from the same vendor to exhibit large differences in electrocatalytic activity and selectivity that arise due to variations in surface faceting. In contrast to Cu, Ag predominately produces H 2 and CO, with CO Faradaic efficiencies exceeding 90% at an applied potential of -1 V vs RHE.…”
Section: Benchmarking Electrocatalytic Performancementioning
confidence: 99%